THE RELATIONSHIP BETWEEN GADGET ADDICTION AND STUDENTS' MENTAL HEALTH: AN ISLAMIC EDUCATIONAL PERSPECTIVE - Muhammad Ridwan Hakim; Nurul Izzah (Karimiyah: Journal of Islamic Literature and Muslim Society, 2025)
This study aims to analyze the relationship between gadget addiction and students' mental health from the perspective of Islamic education. Gadget addiction has become a serious concern among Indonesian students, with demonstrable impacts on multiple dimensions of mental health, including anxiety, depression, sleep disorders, and impaired cognitive functioning. Employing a mixed-methods approach quantitative correlational and qualitative library research the study integrates empirical data analysis (n=284 senior high school students in three major Indonesian cities) with theoretical examination based on Nicholas Carr's The Shallows: What the Internet Is Doing to Our Brains and Islamic educational psychology. Results demonstrate: (1) a significant positive correlation between gadget addiction and anxiety levels (r=0.71, p<0.001) and depression (r=0.64, p<0.001); (2) a negative correlation between gadget addiction and sleep quality (r=-0.68, p<0.001) and academic achievement (r=-0.59, p<0.001); (3) the Islamic perspective identifies gadget addiction as a form of israf (wastefulness) and ghafla (heedlessness), which contradicts the principle of al-'aql (intellect) as a divine trust (amanah) that must be preserved. An intervention model grounded in Islamic Counseling and Guidance (BKI) with a tazkiyatun nafs approach is proposed as a comprehensive solution for addressing gadget addiction among Muslim students.